Pusat Penelitian dan Pengembangan Budidaya Perikanan dengan Pendekatan Arsitektur Biophilic - Irma Dwiyanti; Muhammad Rijal; Wahyu Hidayat (Universitas Medan Area, 2022)
Kampar Regency is one of the regencies with a quit spacious aquaculture area with pisciculture business activities as one of the livelihoods of most of the people. Freshwater fish farming in Kampar Regency includes the pisciculture of karamba or in ponds. The request for freshwater fish production in Riau province is also quite high, such as catfish, carp, tilapia, pomfret and baung fish for daily consumption or industrial needs. The high request for fish production in Kampar regency cannot always be fulfielld. This is due to the failure of aquaculture caused by various factors such as climate, environment, pests and diseases. So to avoid the occurrence of these failures required skilled human resources and adequate facilities. Research and Development Center for Aquaculture which functions as a center for development, research and public education in advancing the community's economy, which includes a research center, laboratory and also commercial functions in the fisheries sector. In designing the Center for Aquaculture Research and Development, the Biophilic architectural approach is used. Biophilic architecture is a good relationship between nature, humans and architecture. The concept of the building takes the concept of